Peranan Supervisi Dalam Meningkatkan Kualitas Pembelajaran Berkelanjutan Di SD Harapan Bangsa Kalimantan Barat - Semoyati Semoyati; Halida Halida; Marinu Waruwu; Eny Enawaty; Fazarudn Fazarudin (Journal on Education, 2024)
Supervision plays a significant role in guiding, developing, and supporting teachers to achieve high learning standards. In education, supervision is not merely a monitoring mechanism but an integral strategy for professional development and the holistic improvement of learning quality. This study aims to analyze the role of supervision in enhancing the quality of continuous learning at Harapan Bangsa Elementary School in West Kalimantan. The research method used is qualitative with a case study design. The subjects of the research include supervisors or principals, teachers, and students. Data were collected through interviews, observations, and documentation, and then analyzed using triangulation techniques. The analysis focuses on identifying the role of supervision, its impact on teachers, its influence on the quality of learning, and its contribution to the professional development of teachers. The results of the study show that supervision plays a crucial role in enhancing teacher professionalism through regular supervision sessions that allow in-depth discussions about teaching methods and learning strategies. Supervision helps teachers adapt to curriculum developments and educational policies. Identifying individual teacher potentials and needs through observation and coaching enables the creation of targeted professional development programs. Furthermore, supervision contributes to the holistic development of learning, including character building, social skills, and students' critical thinking abilities. The implementation of innovative teaching methods is encouraged through supervisory support, which provides resources and related training.